2015
DOI: 10.1016/j.yebeh.2015.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of a behavior-modifying intervention to enhance antiepileptic drug adherence

Abstract: Between 35% and 50% of patients with epilepsy are reported not to be fully adherent to their medication schedule. We aimed to conduct an economic evaluation of strategies for improving adherence to antiepileptic drugs. Based on the findings of a systematic review, we identified an implementation-intention intervention (specifying when, where and how to act) which was tested in a trial that closely resembled current clinical management of patients with epilepsy, and which measured adherence with an objective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…Three studies were identified that looked at the costeffectiveness of epilepsy surgery and compared it with 35 20 2 5 90.9 Beretta et al 47 15 5 7 75.0 Blais et al 36 19 2 6 90.5 Bolin et al 23 17 5 4 77.3 Bowen et al 40 22 1 4 95.7 Chisholm et al 20 16 7 4 69.6 Chisholm et al 21 14 9 4 60.9 Clements et al 39 19 4 4 82.6 Craig et al 32 12 11 4 52.2 De Kinderen et al 44 21 2 3 91.3 De Kinderen et al 43 19 1 7 95.0 Frew et al 33 16 6 5 72.7 Gharibnaseri et al 34 16 5 6 76.2 Gureje et al 22 5 17 5 22.7 Hawkins et al 29 22 0 4 100.0 Helmers et al 45 16 5 6 76.2 Jentink et al 66 31 18 5 4 78.3 Lee et al 51 22 1 4 95.7 Lee et al 52 19 3 5 86.4 Majoie et al 46 11 8 8 57.9 Maltoni and Messori 27 18 5 4 78.3 Marson et al 17 21 1 5 95.5 Noble et al 48 19 1 7 95.0 Oldham et al 42 9 11 7 45.0 Plumpton et al 49 16 6 5 72.7 Rane et al 50 4 16 7 20.0 Remak et al 16 18 5 4 78.3 Remak et al 28 16 5 6 76.2 Simoens et al 24 23 0 4 100.0 Spackman et al 30 20 3 4 87.0 Suh and Lee 37 18 4 5 81.8 Van Hout et al 15 11 11 5 50.0 Vera-Llonch et al 26 18 5 4 78.3 Verdian et al 38 23 0 4 100.0 Widjaja et al 41 18 4 5 81.8 Average quality score: 77.0 "Yes" indicates sufficiently/correctly described and conducted in the study; "No" indicates insufficient, wrong, or no information regarding the specific topic in the study; NA, not applicable. A full description of the items can be found in Appendix S2.…”
Section: Epilepsy Surgerymentioning
confidence: 99%
“…Three studies were identified that looked at the costeffectiveness of epilepsy surgery and compared it with 35 20 2 5 90.9 Beretta et al 47 15 5 7 75.0 Blais et al 36 19 2 6 90.5 Bolin et al 23 17 5 4 77.3 Bowen et al 40 22 1 4 95.7 Chisholm et al 20 16 7 4 69.6 Chisholm et al 21 14 9 4 60.9 Clements et al 39 19 4 4 82.6 Craig et al 32 12 11 4 52.2 De Kinderen et al 44 21 2 3 91.3 De Kinderen et al 43 19 1 7 95.0 Frew et al 33 16 6 5 72.7 Gharibnaseri et al 34 16 5 6 76.2 Gureje et al 22 5 17 5 22.7 Hawkins et al 29 22 0 4 100.0 Helmers et al 45 16 5 6 76.2 Jentink et al 66 31 18 5 4 78.3 Lee et al 51 22 1 4 95.7 Lee et al 52 19 3 5 86.4 Majoie et al 46 11 8 8 57.9 Maltoni and Messori 27 18 5 4 78.3 Marson et al 17 21 1 5 95.5 Noble et al 48 19 1 7 95.0 Oldham et al 42 9 11 7 45.0 Plumpton et al 49 16 6 5 72.7 Rane et al 50 4 16 7 20.0 Remak et al 16 18 5 4 78.3 Remak et al 28 16 5 6 76.2 Simoens et al 24 23 0 4 100.0 Spackman et al 30 20 3 4 87.0 Suh and Lee 37 18 4 5 81.8 Van Hout et al 15 11 11 5 50.0 Vera-Llonch et al 26 18 5 4 78.3 Verdian et al 38 23 0 4 100.0 Widjaja et al 41 18 4 5 81.8 Average quality score: 77.0 "Yes" indicates sufficiently/correctly described and conducted in the study; "No" indicates insufficient, wrong, or no information regarding the specific topic in the study; NA, not applicable. A full description of the items can be found in Appendix S2.…”
Section: Epilepsy Surgerymentioning
confidence: 99%
“…Non-adherence to treatment can be associated with serious issues in patients with epilepsy. 10 As well as being a proven trigger for status epilepticus, 11 non-adherence has been associated with higher rates of hospitalization, 12 worse longterm seizure control 13 and increased healthcare costs, 14 compared with patients who are adherent. Therefore, when making treatment decisions, factors affecting compliance should always be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Published evidence suggests that adherence-enhancing interventions are cost-effective or cost-saving 31,32. However, more studies on the cost-effectiveness of pharmacist-delivered interventions to improve adherence are needed.…”
Section: Discussionmentioning
confidence: 99%